IMAM AL - GHAZALI'S EDUCATIONAL LEADERSHIP MODEL - Iwan Setiawan; Anis Fauzi; Machdum Bachtiar (Media Inovasi Pendidikan dan Publikasi, 2024)
Imam Al-Ghazali's educational leadership model is a leadership approach based on the teachings and thoughts of the famous Islamic philosopher, Imam Al-Ghazali. Imam Al-Ghazali was an 11th century Islamic scholar known for his contributions to the fields of philosophy, theology, and education. This educational leadership model combines the principles of Islamic education with the leadership concept developed by Imam Al-Ghazali. In this model, educational leadership is seen as a very important role in guiding and motivating students and educational staff members to achieve their educational goals. Imam Al-Ghazali emphasized the importance of fair, wise and moral leadership in the context of education. This model outlines several main principles underlying Imam Al-Ghazali's educational leadership; Leadership Based on Islamic Values, Deep Understanding of Students, Personality Development, Exemplary Leadership, Teamwork and Consultation, Continuous Education Improvement, Imam Al-Ghazali's educational leadership model encourages a holistic approach in education that includes Islamic moral and ethical aspects . This creates an educational environment that supports the development of students' character and personality and helps them become better individuals in society. By following these principles, educational leaders can become agents of positive change in the world of Islamic education.